2018
DOI: 10.2196/jmir.9436
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Health Information Technologies Among US Adults: Analysis of the Health Information National Trends Survey

Abstract: BackgroundEmerging health technologies are increasingly being used in health care for communication, data collection, patient monitoring, education, and facilitating adherence to chronic disease management. However, there is a lack of studies on differences in the preference for using information exchange technologies between patients with chronic and nonchronic diseases and factors affecting these differences.ObjectiveThe purpose of this paper is to understand the preferences and use of information technology… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 50 publications
5
38
0
Order By: Relevance
“…Although many previous studies have already proven that younger age is associated with m-health app engagement,26,27 older people do not refuse to become involved with this new m-health technology. In contrast, Russell28 found that older people had a positive attitude toward health-related apps, and Jonathan23 observed that older respondents showed the same willingness to engage with m-health apps as younger respondents.…”
Section: Discussionmentioning
confidence: 99%
“…Although many previous studies have already proven that younger age is associated with m-health app engagement,26,27 older people do not refuse to become involved with this new m-health technology. In contrast, Russell28 found that older people had a positive attitude toward health-related apps, and Jonathan23 observed that older respondents showed the same willingness to engage with m-health apps as younger respondents.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that frequent users of health services, such as people with diabetes or other chronic diseases, are more likely to use the internet for health information compared with nonusers [6,21], which might explain some differences in the rates. On the other hand, a recent study found that demographic differences were more important than the presence or absence of chronic disease in this regard [34]. Other possible explanations might be cultural differences and differences in the level of exposure to internet information, the need for regular as well as irregular doctor visits, and the ability to apply internet information to one’s own health situation.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of diabetes-specific HIE, several authors concentrated on the patients’ role in information sharing [21,22]. HIE between DM patients and care providers was examined with a focus on sharing medication data [23], email communication [24], and patient preferences [25].…”
Section: Discussionmentioning
confidence: 99%